Chemical Profile, Antioxidant and Cytotoxic Potencies and Docking Study of Semipolar Fraction of Nepthea sp. - Sahidin Idin; Sadarun Baru; Fristiohady Adryan; Syifa Rahmatika Nur; Wibawa Mahatva Yodha Agung; Arfan; Sundowo Andini; Fajriah Sofa (BIO Web of Conferences, 2024)
The aims of research is to explore pharmaceutical and chemicals aspects of Nepthea sp. The methods include fractionation of ethylacetate extract (EAE) by vacuum liquid chromatrography (VLC). The chemical content was evaluated by LC-MS/MS analysis, phytochemical screening, Total Phenolics Content (TPC) and Total Flavonoids Contents (TFC). Antioxidant and cytotoxic potencies were evaluated by DPPH/ABTS methods and MTT assays and also docking study. Fractionation of EAE produced six fractions (1-6). Fraction 3 and 4 were semi-polar compounds, which contained terpenoids, phenolics and alkaloids. According to LCMS/MS, the identified semi-polar compounds consist of 3-acetyl-3,4-dihydro-5,6-dimethoxy-2(1)H-benzopyrone and oxyphyllenone B from Fraction 3 and 1-(4-hydroxy-3-methoxy)-phenyl-1,2,3-propanetriol, digiprolactone, petasitolone, δ-humulene, rengyolester, and piperolactam-C9:1(8E) for Fraction 4. The antioxidant potency of fraction 4 was better than Fraction 3. Based on IC50 value, Fraction 3 is active category and Fraction 4 is moderately active against MCF-7 cell lines. At the molecular level, rengyolester and piperolactam-C9:1(8E) revealed potential antioxidant activity by inhibiting XO, which was correlated with antiradical in vitro results. Meanwhile, the anticancer activity of oxyphyllenone B and piperolactam-C9:1(8E) demonstrated a higher affinity for inhibiting ERα than other compounds. As conclusion, semipolar fractions of EAE have good potential as an antioxidant and cytotoxic agent against MCF-7 cell lines.